The Mental Health State and Psychological Well-Being of School Teachers during COVID-19 Pandemic in Malaysia - Aina Mardhiah Rosli; Abu Yazid Abu Bakar (Department of Guidance and Counseling, FIP, Undiksha, 2021)
This study was conducted to determine the level of mental health and psychological well-being of school teachers during the Movement Control Order (MCO) enforced throughout COVID-19 pandemic in Malaysia. The study sample consisted of 274 male and female school teachers in Selangor state, Malaysia. This quantitative data was obtained using an online questionnaire developed via 'Google form' application, and was analyzed using SPSS software version 28.0. Perceived Stress Scale (COVID-19 PSS-10) English Version shows Alpha Cronbach's value of α = 0.719. The validity test of the instrument Ryff's Psychological Well-Being Scale (PWB) English Version shows the alpha Cronbach's α = 0.86. The set of questionnaires was analyzed descriptively, independent sample t - test was also conducted. The study found that respondents have a moderate level of psychological well-being. There were no significant differences between the genders of teachers. The findings of the study are expected to help reduce the level of stress faced by teachers’ aims to preserve their psychological health in order to ensure the well-being of students and the continuity of the national education system